Susceptibilty Test for Road Construction: A Case Study of Shake Road, Irrua, Edo State (Global Journal of Science Frontier Research, 2019)
This research showed the significance of electrical resistivity method for road construction along Shake road, Irrua, Edo State, Nigeria. The aim of the study is to establish the near surface geological features that are predisposed to incessant case(s) of road failures few months or years after construction. The geophysical investigation involved three techniques; Vertical Electrical Sounding (VES), 2-D Electrical Resistivity Tomography (ERT) and Horizontal Profiling (HP) which covers a pilot test of 220 meters. Ten (10) VES were carried out using Schlumberger array with current electrode spacing varying from 1.00 to 100.00 m, with 2-D ERT using Dipole-Dipole electrode array with inter-station separation of 10 m and an expansion factor that varied from 1 to 5 and HP using Wenner array with an electrode spacing of 5 m interval. The VES interpretation results were used to determine the second order parameters for determination of integrity and susceptibility test of failure. The result obtained from the VES delineated three geoelectric units which Comprise of topsoil, clay layer, sand layer/shale horizon units. The 2 D imaging (Dipole-Dipole) gave information on the subsurface characteristic which indicates high, moderately high integrity and low integrity/a low competence material. The Wenner profile is characterised by low resistivity.
Keywords: integrity test; susceptibility test; dipole-dipole; geoelectric section; longitudinal conductance